A Revised Diagnosis of Palaeodysagrion cretacicus Zheng et al., 2016 (Insecta: Odonata) from mid-Cretaceous Burmese Amber, with erection of a new genus of fossil damselflies - Bechly, Günter; Velten, Jürgen (Zootaxa, 2023)
The diagnosis of Palaeodysagrion cretacicus Zheng et al., 2016 is revised based on the description of a new specimen from mid-Cretaceous Burmese amber. Previously, only a fragmentary wing base was known from the holotype. The new specimen shows the complete wing venation of fore- and hind wings as well as large parts of the body anatomy. The new information proves that Palaeodysagrion youlini Zheng et al., 2017 has a very different venation and does not belong to the same genus. Therefore, a new genus Pseudopalaeodysagrion gen. nov. is erected for this species. Concurring with the results of Archibald et al. (2021), the “dysagrionine” taxa from Burmese amber are transferred from Dysagrionidae to Burmadysagrionidae stat. nov.